Analisis Implementasi Supply Chain Management Dalam Meningkatkan Kinerja Operasional Studi Kasus: PT Bintang Samudra Indonusa - Dianita Ayu Oktaviani; Rediawan Miharja (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2025)
Supply Chain Management is a strategy for addressing challenges and an effort to enhance performance quality, thereby maintaining and creating a competitive advantage. This research was conducted to analyzed the network structure, business processes, and implementation of supply chain management (SCM) in improving operational performance at PT Bintang Samudra Indonusa. This research uses a descriptive quantitative method with the SCOR model approach, namely plan, source, make, deliver, and return and calculation with AHP through pairwise comparison. The results showed that the network structure at PT Bintang Samudra Indonusa has three parts. The planning process is the highest priority in supporting the company's SCM performance and in the implementation of SCM performance that has been carried out at PT Bintang Samudra Indonusa several indicators have not reached the optimal value, especially in the planning process. Thus, the company needs to make improvements related to these indicators so that operational performance runs optimally and increases.